2019
DOI: 10.1186/s10194-018-0953-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of onabotulinumtoxinA treatment in chronic migraine patients with and without daily headache at baseline: results from the COMPEL Study

Abstract: BackgroundOnabotulinumtoxinA is effective in preventing chronic migraine (CM); however, the benefit of onabotulinumtoxinA in patients with CM with daily headache is unknown because these patients are typically excluded from clinical trials. This subanalysis of the COMPEL Study assessed the efficacy and safety of onabotulinumtoxinA in people with CM with and without daily headache.MethodsIn total, 715 patients received onabotulinumtoxinA 155 U with or without concomitant oral preventive treatment. Patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
2
16
1
5
Order By: Relevance
“…In addition, our data support strong clinically and statistically significant associations between health-related quality of life in patients with CM and BONT-A. The results from this real-world study are consistent with the efficacy and safety profile of BNT-A established in clinical trials [4, 7] and other studies [9-11]. All these factors require the patient and physician to have a good understanding of the disease, its course, and to work together to achieve the best outcome.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, our data support strong clinically and statistically significant associations between health-related quality of life in patients with CM and BONT-A. The results from this real-world study are consistent with the efficacy and safety profile of BNT-A established in clinical trials [4, 7] and other studies [9-11]. All these factors require the patient and physician to have a good understanding of the disease, its course, and to work together to achieve the best outcome.…”
Section: Discussionsupporting
confidence: 90%
“…At baseline, the median (Q1-Q3) number of migraine days was 12 (10)(11)(12)(13)(14)(15). The number of median migraine days reduced to 8 (6-9) at 6 months (p < 0.001) and to 5 (4-7) at 12 months (p < 0.001) ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…In other analyses of BoNT/A efficacy in COMPEL [ 16 , 27 – 37 ] (post hoc [ 27 , 35 , 36 ], where stated): Assessments of migraine-related disability (MIDAS score) [ 28 ] and migraine-specific HR-QOL (all three MSQ domain scores) were improved ( p < 0.0001 vs baseline) at week 108 [ 28 ] Comorbid symptoms of depression [measured using the 9-item Patient Health Questionnaire (PHQ-9)] and anxiety (7-item Generalized Anxiety Disorder Assessment), and associated symptoms of sleep disturbance (Pittsburgh Sleep Quality Index) and fatigue (Fatigue Severity Scale), were improved ( p < 0.0001 vs baseline) at week 108; similar improvements were seen at all earlier assessments [ 29 ] Assessments of headache symptoms [ 16 , 30 34 ], headache-related impact (HIT-6 score) [ 16 , 30 , 33 ], migraine-related disability (MIDAS score) [ 31 , 32 , 34 ] and migraine-specific HR-QOL (all three MSQ domain scores) [ 32 , 34 ] were improved to a similar extent in patients with or without a history of acute medication overuse [ 30 , 31 ], those receiving or not receiving oral preventive treatments at baseline [ 16 ], those with or without daily headaches at baseline [ 32 , 33 ], and those with or without allodynia at baseline [ 34 ] The proportion of monthly headache-day frequency responders progressively increased over the course of the study (47%, 54%, 57% and 62% at weeks 24, 60, 84, 108, respectively). Among patients who completed all nine treatment cycles, a high proportion (76%) of monthly headache-day frequency responders at week 24 maintained this response through week 108 [ 35 ] Responder rates at week 108 were 62% for monthly headache-day frequency, 59% for HIT-6 score, 75% for MIDAS score and 66% for MSQ RR domain score; 87%, 72%, 52% and 27% of patients achieved at least one, at least two, at least three or all four of these outcomes, respectively [ 27 ] The proportion of patients who achieved treatment-controlled CM (defined as < 15 headache days/month in any of the 4-week periods ending at weeks 24, 60, 84 and 108) was high and increased progressively over the course of the study (56%, 69%, 70% and 74% at weeks 24, 60, 84 and 108, respectively) [ 36 ] Sustained treatment-controlled CM (defined as &...…”
Section: What Is the Clinical Efficacy Of Onabotulinumtoxina In Chronmentioning
confidence: 93%
“…Assessments of headache symptoms [ 16 , 30 34 ], headache-related impact (HIT-6 score) [ 16 , 30 , 33 ], migraine-related disability (MIDAS score) [ 31 , 32 , 34 ] and migraine-specific HR-QOL (all three MSQ domain scores) [ 32 , 34 ] were improved to a similar extent in patients with or without a history of acute medication overuse [ 30 , 31 ], those receiving or not receiving oral preventive treatments at baseline [ 16 ], those with or without daily headaches at baseline [ 32 , 33 ], and those with or without allodynia at baseline [ 34 ]…”
Section: What Is the Clinical Efficacy Of Onabotulinumtoxina In Chronmentioning
confidence: 99%
“…The COMPEL study, a large long-term open-label study funded by Allergan, further explored the type of chronic migraine patient who responded to OBTA. It found that in the long term, patients with daily headache had a very similar reduction in the number of moderate or severe headache days per month as patients without daily headache at baseline [ 22 ].…”
Section: Modern Clinical Trials In Migrainementioning
confidence: 99%